Prediksi Kategori Serangan Siber dengan Algoritma Klasifikasi Random Forest Menggunakan Rapidminer - Saddam Rabbani; Diana Diana (SMATIKA JURNAL : STIKI Informatika Jurnal, 2023)
Cyber attacks are a serious threat to organizations or institutions that use computer networks in their operations, one of which is Communication and Informatics Department of Palembang. Therefore, this study aims to implement the Random Forest classification algorithm on the Rapidminer platform to predict cyber attack categories at the Communication and Informatics Department of Palembang. The data used in this study is cyber attack data from firewall devices for a certain period. The data is processed using Rapidminer with the Random Forest algorithm to predict cyber attack categories. The results of this research provide a high accuracy value, thereby enabling the responsible team to take preventive action or response detrimental cyber to the Communication and Informatics Department of Palembang. After evaluation using the confusion matrix and accuracy score, the results obtained were 99.84% accuracy and out of bag error 0.16.